THE AUTHORITY OF THE COUNCIL OF REPRESENTATIVES OF THE REPUBLIC OF INDONESIA (DPR RI) IN RATING INTERNATIONAL AGREEMENTS POST THE RULING OF THE CONSTITUTIONAL COURT (MK) NUMBER 13/PUU-16/2018 - Bah Jatun Nadrati; Risnain, Muh; Zunnuraeni (Department of Law, Faculty of Law, University of Mataram, 2024)
This research aims to find out and understand the meaning of the DPR RI's authority to ratify international agreements based on Constitutional Court Decision No. 13/PUU-16/2018 and to understand and analyze the direction of regulating the authority of the DPR RI in ratifying international agreements after Constitutional Court Decision No. 13/PUU-16/2018. This research method uses a type of normative legal research. The meaning of the DPR RI's authority to ratify international agreements based on Constitutional Court Decision No. 13/PUU-16/2018 expands the definition of DPR approval, which is not limited to the provisions of Article 10 of Law no. 24 of 2000 concerning international agreements, but in all international agreements which have the nature of having broad and fundamental consequences for people's lives related to the financial burden on the state, and requiring changes or formation of laws. The Constitutional Court's decision pertaining to the DPR's authority in ratifying international agreements, the Constitutional Court expanded the meaning of Article 10 by cancelling the Article and returning to the norms contained in article 11 of the 1945 Constitution of the Republic of Indonesia, the Constitutional Court interpreted it extensively. The direction of regulating the authority of the DPR RI in ratifying international agreements after the Constitutional Court decision no. 13/PUU-16/2018 is by changing or replacing the existing norms in article 10 of Law No. 24 of 2000 concerning International Agreements by regulating the substance of international agreements as intended in article 11 of the 1945 Constitution of the Republic of Indonesia and following the pattern of article 84 of Law no. 7 of 2014.